The Occasional Evil of Angels: Learning from the Experiences of Aboriginal Peoples and Social Work - Blackstock, Cindy (First Peoples Child & Family Review, 2009)
This paper explores how the propensity of social workers to make a direct and unmitigated connection between good intentions, rationale thought and good outcomes forms a white noise barrier that substantially interferes with our ability to see negative outcomes resulting directly or indirectly from our works. The paper begins with outlining the harm experienced by Aboriginal children before moving to explore how two fundamental philosophies that pervade social service practice impact Aboriginal children: 1) an assumption of pious motivation and effect and 2) a desire to improve others. Finally, the paper explores why binding reconciliation and child welfare is a necessary ﬁrst step toward developing social work services that better support Aboriginal children and families.